The Importance of Building Communication Awareness as an Effort for Sustainable Conflict Resolution in West Kalimantan - Jagad Aditya Dewantara; Muhammad Jailani; Syamsuri Syamsuri; Efriani Efriani; Sulistyarini Sulistyarini; T Heru Nurgiansah (Universitas of Muhammadiyah Makassar, 2023)
This article stems from the social gap felt by the Chinese ethnic community in a multiethnic environment, which requires them to be able to blend in and interact with each other. As multicultural ethnic life requires them to understand and establish social relationships with each other, communication awareness becomes an important aspect in preventing conflicts that often arise due to misunderstandings among the multiethnic community. This study aims to analyze the community's communication practices among ethnic groups as an effort to bridge and overcome social gaps post-conflict. The research was conducted using ethnographic methodology to reveal facts by employing observation, interviews, and documentation to gather data. The research informants were 12 individuals, consisting of four Chinese ethnic members and eight local community members. The results reveal that the Chinese ethnic group has implemented several strategies to build communication awareness when interacting with the diverse local community. These strategies include self-awareness of diversity values, building genuine tolerance in the community, the readiness and willingness to engage in open communication, and being good listeners.